2018
DOI: 10.1074/jbc.m117.811737
|View full text |Cite
|
Sign up to set email alerts
|

The Salmonella effectors SseF and SseG inhibit Rab1A-mediated autophagy to facilitate intracellular bacterial survival and replication

Abstract: In mammalian cells, autophagy plays crucial roles in restricting further spread of invading bacterial pathogens. Previous studies have established that the virulence factors SseF and SseG are required for intracellular bacterial survival and replication. However, the underlying mechanism by which these two effectors facilitate bacterial infection remains elusive. Here, we report that SseF and SseG secreted by Typhimurium ( Typhimurium) inhibit autophagy in host cells and thereby establish a replicative niche f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 52 publications
(46 reference statements)
0
31
1
Order By: Relevance
“…We now expand this interaction by showing the physiological relevance of RAB1A in SIF formation (Figure 4), as well as the presence of both RAB1A and RAB1B on SIF (Figure 5). This is in striking contrast to the previous observation that RAB1A is detrimental to STM replication due to its role in antibacterial autophagy, which is counteracted by the SPI2-T3SS effectors SseFG [93, 94]. Future work has to clarify this apparent conundrum, at least regarding RAB1A.…”
Section: Discussioncontrasting
confidence: 65%
“…We now expand this interaction by showing the physiological relevance of RAB1A in SIF formation (Figure 4), as well as the presence of both RAB1A and RAB1B on SIF (Figure 5). This is in striking contrast to the previous observation that RAB1A is detrimental to STM replication due to its role in antibacterial autophagy, which is counteracted by the SPI2-T3SS effectors SseFG [93, 94]. Future work has to clarify this apparent conundrum, at least regarding RAB1A.…”
Section: Discussioncontrasting
confidence: 65%
“…Additionally, the role of effector protein SseL is quite specific in that it deubiquitinates ubiquitin aggregates on the surface of SCV, thereby decreasing its targeting to the autophagosomes ( Mesquita et al, 2012 ). Another effectors from Salmonella , SseF and SseG inhibits autophagosome formation by disrupting Rab1-A signaling ( Feng et al, 2018 ). Although, many bacterial proteins are known to disrupt the autophagy pathway indirectly, RavZ, which is a T4SS effector of Legionella pneumophila is the only identified bacterial factor that directly inhibits components of the autophagy pathway.…”
Section: Bacterial Effectors In Selective Autophagy (Xenophagy) Durinmentioning
confidence: 99%
“…L. monocytogenes inhibits xenophagy via recruiting the Arp2/3 complex and Ena/VASP to the bacterial surface, where it masks the cell surface by binding to the cytoplasmic major vault protein (MVP) or blocking the lipidation of LC3 [132][133][134]. Salmonnella typhimurium secrets more than 30 effector proteins, resulting in the mTOR activation [135], deubiquitination of aggregates [136], and disrupting Rab1-A signal [137], and ultimately, autophagy suppression. In their most recent study, Shao Feng's lab found that a novel protein, SopF, generated by Salmonella inhibit xenophagy by targeting the Gln124 of ATP6V0C in the V-ATPase, resulting in disruption of V-ATPase-ATG16L1 axis in xenophagy initiation [138].…”
Section: Xenophagymentioning
confidence: 99%